Naiju Jose Kalambukattu and Benny Thettayil, ed., The Stunned Populace, Religio-Political Manoeuvres in India: A Theological Response (Samanvayam Contextual Theology Series 10 & Sadharmayam Research Series 2), Bengaluru: Dharmaram Publications, 2020 - Pendanath, Jerin Thomas (Asian Horizons, 2020)
Naiju Jose Kalambukattu and Benny Thettayil, ed., The Stunned Populace, Religio-Political Manoeuvres in India: A Theological Response (Samanvayam Contextual Theology Series 10 & Sadharmayam Research Series 2), Bengaluru: Dharmaram Publications, 2020, Pages xii+324. ISBN 978-81-945014-2-8